A model for mapping of Ebola and Marburg RNA integration sites in rhesus Macaca mulatta genome in silico: Ebola virus acceptors sites located on chromosomes 4, 6, 7, 8, 9, 14 and 15 - Misaki, Wayengera; Wilson, Byarugaba; Henry, Kajjumbula; Olobo, J.; Mulindwa, Kaddu (African Journal of Biotechnology, 2009)
Viral integration into the host genetic material is necessary for replication and survival, since viruses are obligate intracellular organisms. Understanding of the exact loci of integration may thus provide targets for future therapeutic and vaccine strategies, pathogenesis elucidation, as well as a model for the evolutionary trends of successful viral cross over. Although the exact natural reservoir for the filovirade family of viruses still remains elusive, most index cases in human outbreaks have been linked to contact with nonhuman primates (NHP). We hypothesized that homogeneity between viral integration complex and host genome may be a major predictor of integration. To investigate and map the loci of integration of the two major genes of this family of viruses within NHP genomes, we queried both Ebola and Marburg Glycoprotein (GP) gene sequences against the whole genome of rhesus macaque using BLAST-N analysis. Of all the contigs length 2.87 Gb (2,863,665,185) bases in the genome of rhesus macaque, Marburg GP blast hits to rhesus genome nucleotide database were 6,451,736 compared to 4,012,901 for Ebola. Marburg GP genomic RNA had 18 alignments located on undefined scaffolds compared to 7 of Ebola located on chromosomes 4, 6, 7, 8, 9, 14 and 15. We also found an efficiency of 66.6% within Marburg GP alignments compared to 100% for Ebola. Our results serve to demonstrate that although Marburg GP RNA acceptors are more prevalent in the Rhesus genome than ebola; their loci of integration are vaguely defined compared to Ebola. If the level of homogeneity between acceptors and PIC has no effect of integration, then Marburg may be better adapted to integrate into Rhesus that Ebola. Alternatively, chromatic DNA might be a more effective target for future Ebola genomic vaccines sequestered at a nuclear location inaccessible to incoming Pre-integration Complexes (PICs-which in this model are Ebola glycoprotein gene complexes) than Marburg.
Keywords: Ebola; Marburg; In-vivo integration; Rhesus macaca; Line elements; Insilico genomics